Safety of first year vaccination in children born to mothers with inflammatory bowel disease and exposed in utero to anti‐TNFα agents: a French nationwide population‐based cohort. Issue 11 (15th October 2019) - Luu, Maxime; Benzenine, Eric; Barkun, Alan; Doret, Muriel; Michiels, Christophe; Degand, Thibault; Quantin, Catherine; Bardou, Marc
Summary: Background: Children born to mothers with IBD may be exposed to anti‐TNFα agents antenatally. Current European guidelines recommend postponing live vaccines until after 6 months of life in this population. Data on the safety of live vaccines administration in the first year of life of these children are sparse with one reported fatality following bacillus Calmette‐Guerin (BCG) administration. Aims: To describe the use and safety of vaccines administered in children born to mothers with IBD and exposed antenatally to anti‐TNFα agents Methods: Data from children born to mothers with IBD between 2013 and 2014 were collected retrospectively from the French Health Insurance Database. Vaccines recommended before or at 1 year of age were considered. Results: Among 4741 children, 670 (14.1%) were exposed to anti‐TNFα agents antenatally, with concomitant thiopurines in 16.0% (n = 107) and steroids in 19.3% (n = 214). Among these 670 children, 315 (47%) were exposed up to delivery. Exposed children were less likely than non‐exposed to receive BCG (88/670, 13.1% vs 780/4071, 19.2% respectively, P < .05) and received it later in life (months, mean ± SD, 4.3 ± 3.9 and 2.4 ± 2.9 respectively, P < .001). In exposed children, 64/88 (73%) received BCG vaccination before 6 months of age, but with no BCG‐related severe adverse event observed during the first year. Uptake of other vaccines recommended before 6 months was above 85% in both groups. Conclusion: In children exposed antenatally to anti‐TNFα agents, vaccinations are often not postponed in keeping with the recommendations, but no BCG‐related severe adverse events were reported in children vaccinated before 6 months of life.